The MAVERIC survey: a hidden pulsar and a black hole candidate in ATCA radio imaging of the globular cluster NGC 6397 - Zhao, Yue; Heinke, Craig O; Tudor, Vlad; Bahramian, Arash; Miller-Jones, James; Sivakoff, Gregory R; Strader, Jay; Chomiuk, Laura; Shishkovsky, Laura; Maccarone, Thomas J; Marcano, Manuel Pichardo; Gelfand, Joseph D (OXFORD UNIV PRESS, 2020)
Using a 16.2 hr radio observation by the Australia Telescope Compact Array (ATCA) and archival Chandra data, we found $>5σ$ radio counterparts to 4 known and 3 new X-ray sources within the half-light radius ($r_h$) of the Galactic globular cluster NGC 6397. The previously suggested millisecond pulsar (MSP) candidate, U18, is a steep-spectrum ($S_ν \propto ν^α$; $α=-2.0^{+0.4}_{-0.5}$) radio source with a 5.5 GHz flux density of $54.7± 4.3~μ Jy$. We argue that U18 is most likely a "hidden" MSP that is continuously hidden by plasma shocked at the collision between the winds from the pulsar and companion star. The nondetection of radio pulsations so far is probably the result of enhanced scattering in this shocked wind. On the other hand, we observed 5.5 GHz flux of the known MSP PSR J1740-5340 (U12) to decrease by a factor of $>2.8$ during epochs of 1.4 GHz eclipse, indicating that the radio flux is absorbed in its shocked wind. If U18 is indeed a pulsar whose pulsations are scattered, we note the contrast with U12's flux decrease in eclipse, which argues for two different eclipse mechanisms at the same radio frequency. In addition to U12 and U18, we also found radio associations for 5 other Chandra X-ray sources, four of which are likely background galaxies. The last, U97, which shows strong H$α$ variability, is mysterious; it may be either a quiescent black hole low-mass X-ray binary, or something more unusual.